Showdown with the shepherd - Hering, Marianne; Eastman, Brock, 1983-; McCusker, Paul, 1958-; Hohn, David, 1974- (Carol Stream, Ill. : Tyndale House Publishers, 2011)
Mr. Whittaker uses the Imagination Station to transport cousins Patrick and Beth to the Holy Land in 1000 B.C., where Hugh is trying to change history by helping the Philistines defeat the Israelites.
"A Focus on the Family book"--T.p. verso.
Ages 7 and up.
Grade Level: 2.0.
Keywords: David, -- King of Israel -- Fiction; Space and time -- Fiction; Philistines -- Fiction; Cousins -- Fiction; Christian life -- Fiction; Palestine -- History -- To 70 A.D. -- Fiction